Legal Views of Religious Leaders of Simangambat District, North Padang Lawas Regency Regarding Attending the Invitation of Walimatul 'Ursy Who Carried Out Endeng-Endeng - Hotma Pasaribu; Ibnu Radwan Siddik Turnip (Warmadewa Press, 2024)
This research is motivated by a social phenomenon about the Endeng-Endeng tradition in Walimatul 'Ursy in Simangambat Village, North Padang Lawas Regency which has often occurred. This study aims to find out how the legal views of religious leaders in Simangambat District regarding the legal status of attending the invitation of Walimatul 'Ursy who carry out Endeng-Endeng. This research is an empirical legal research with a legal sociology approach, primary data sources are obtained from interviews with a number of religious and community leaders, and the author's observations. Secondary data sources are obtained from a number of references and research results. Data analysis is used using qualitative analysis. The results of the study show that the legal view of religious leaders in Simangambat District allows them to attend Walimatul 'Ursy who carries out Endeng-Endeng, if there are no elements of immorality in it such as liquor. However, if the Endeng-Endeng activity contains elements of showing off birahi, because those who are not mahrams gather to perform the Endeng-Endeng dance, and there are intoxicating drinks, then the ruling is makruh which if not attended will be better. Religious leaders also suggested that it was better to attend Walimatul 'Ursy after the Endeng-Endeng event on the grounds that rejecting affirmation took precedence over obtaining benefits.